Enhanced mesophilic anaerobic digestion of food waste by thermal pretreatment: Substrate versus digestate heating. (December 2015) - Ariunbaatar, Javkhlan; Panico, Antonio; Yeh, Daniel H.; Pirozzi, Francesco; Lens, Piet N.L.; Esposito, Giovanni
Highlights: Thermal pretreatment could enhance biomethanation by more than 40%. The main effect of the pretreatments was increased solubilization of COD. Conventional thermal pretreatment at 80 °C for 1.5 h resulted in the highest BMP. Similar enhancement was obtained with thermophilic pretreatment at 50 °C for 6–12 h. Thermal pretreatment is more energy efficient than thermophilic pretreatment. Abstract: Food waste (FW) represents a source of high potential renewable energy if properly treated with anaerobic digestion (AD). Pretreating the substrates could yield a higher biomethane production in a shorter time. In this study, the effects of thermal (heating the FW in a separate chamber) and thermophilic (heating the full reactor content containing both FW and inoculum) pretreatments at 50, 60, 70 and 80 °C prior to mesophilic AD were studied through a series of batch experiments. Pretreatments at a lower temperature (50 °C) and a shorter time (<12 h) had a positive effect on the AD process. The highest enhancement of the biomethane production with an increase by 44–46% was achieved with a thermophilic pretreatment at 50 °C for 6–12 h or a thermal pretreatment at 80 °C for 1.5 h. Thermophilic pretreatments at higher temperatures (>55 °C) and longer operating times (>12 h) yielded higher soluble chemical oxygen demand (CODs), but had a negative effect on the methanogenic activity. The thermal pretreatments at the same conditions resulted in a lower solubilization of COD. Based on net energy calculations, the enhanced biomethane production is sufficient to heat up the FW for the thermal, but not for the thermophilic pretreatment.